2015
DOI: 10.1002/2015pa002884
|View full text |Cite
|
Sign up to set email alerts
|

Heinrich 0 on the east Canadian margin: Source, distribution, and timing

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…The possibility that BBDC 1 was synchronous with the North Atlantic Heinrich Event 0 can also be rejected. Although Bond et al, (1997) suggested H0 onset at ~12.8 kyr BP, more recent work (Hillaire-Marcel and de Vernal, 2008;Jennings et al, 2015;Pearce et al, 2015), points to a much younger age ~11.5 kyr BP, at the very end of the Younger Dryas (Figures 4 and 7). The onset of BBDC 1 inferred in this study (~14.1 kyr BP) is ~2400 years younger than the revised onset of H0.…”
Section: Pearce Et Al 2015) Previous Radiocarbon Chronologies In Bmentioning
confidence: 89%
See 2 more Smart Citations
“…The possibility that BBDC 1 was synchronous with the North Atlantic Heinrich Event 0 can also be rejected. Although Bond et al, (1997) suggested H0 onset at ~12.8 kyr BP, more recent work (Hillaire-Marcel and de Vernal, 2008;Jennings et al, 2015;Pearce et al, 2015), points to a much younger age ~11.5 kyr BP, at the very end of the Younger Dryas (Figures 4 and 7). The onset of BBDC 1 inferred in this study (~14.1 kyr BP) is ~2400 years younger than the revised onset of H0.…”
Section: Pearce Et Al 2015) Previous Radiocarbon Chronologies In Bmentioning
confidence: 89%
“…Within these poorly constrained age brackets, BBDC 0 from our records would then be coeval with the start of Heinrich Event 0. However all higher resolution cores present a revised timing of the Heinrich Event 0 onset following the Younger Dryas interval at ~11.5 kyr (Hillaire-Marcel and de Vernal, 2008;Jennings et al, 2015;Pearce et al, 2015) (Figures 4 and 7). This suggests that the onset of ice-sheet instabilities of the northern Baffin Bay predates the H0 discharge from Hudson Strait recorded mostly in the western Labrador Sea.…”
Section: Asynchronous Ice Sheet Instability During the Last Deglaciationmentioning
confidence: 97%
See 1 more Smart Citation
“…It is possible that this is due to data-collection issues (e.g., few organics) and data sparsity (few settlements and fewer GPS monuments) in this formerly fully ice-covered region, leading to a lack of good regional constraints on ice-sheet thickness near the center of the Laurentide Ice Sheet. However, recent data sets have brought more clarity to the Hudson Strait record (e.g., Rashid et al, 2014;Gil et al, 2015;Pearce et al, 2015;Pearce, 2015;Jennings et al, 2015), furthering the argument that this mismatch could be because the models do not accurately represent the dynamics of the marine-terminating Hudson Strait ice catchment (e.g., MacAyeal, 1993). An additional complication of Hudson Bay/Strait is that its drainage area was smaller at the LGM (Fig.…”
Section: Comparison Of Data and Models For River Dischargementioning
confidence: 99%
“…The Hudson Strait Record is difficult to match because of its many episodic meltwater releases (e.g., Heinrich, 1988;Andrews and MacLean, 2003;Hemming, 2004;Gil et al, 2015;Jennings et al, 2015), and only the climate-forced and ice-physics-based G12 reproduces the general form of these events. These events are simplified or smoothed-over by Licciardi et al (1999), but recent improvements in the age constraints on these iceberg and/or meltwater release events (e.g., Rashid et al, 2014;Gil et al, 2015;Pearce et al, 2015;Pearce, 2015;Jennings et al, 2015) set the stage for forthcoming advances in reconstructions of the northeastern core of the Laurentide Ice Sheet.…”
Section: Comparison Of Data and Models For River Dischargementioning
confidence: 99%